2002
DOI: 10.1128/mcb.22.7.2398-2409.2002
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Cleavage of Cyclin E Leads to Inactivation of Associated Kinase Activity and Amplification of Apoptosis in Hematopoietic Cells

Abstract: Cyclin E/Cdk2 is a critical regulator of cell cycle progression from G 1 to S in mammalian cells and has an established role in oncogenesis. Here we examined the role of deregulated cyclin E expression in apoptosis. The levels of p50-cyclin E initially increased, and this was followed by a decrease starting at 8 h after treatment with genotoxic stress agents, such as ionizing radiation. This pattern was mirrored by the cyclin E-Cdk2-associated kinase activity and a time-dependent expression of a novel p18-cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 59 publications
8
62
1
Order By: Relevance
“…The cyclin E1 complex was active at 16 h after treatment, which was earlier than cyclin A or cyclin B1 complexes. In contrast to previous reports, we did not detect small p18 forms of cyclin E that might induce activated CDK complexes (Porter et al, 2001;Mazumder et al, 2002) although the same antibody was used. A role for cyclin B1 in apoptosis A Borgne et al Several lines of evidence support the hypothesis that active CDK complexes participate in CPT-induced apoptosis.…”
Section: Discussioncontrasting
confidence: 99%
“…The cyclin E1 complex was active at 16 h after treatment, which was earlier than cyclin A or cyclin B1 complexes. In contrast to previous reports, we did not detect small p18 forms of cyclin E that might induce activated CDK complexes (Porter et al, 2001;Mazumder et al, 2002) although the same antibody was used. A role for cyclin B1 in apoptosis A Borgne et al Several lines of evidence support the hypothesis that active CDK complexes participate in CPT-induced apoptosis.…”
Section: Discussioncontrasting
confidence: 99%
“…During apoptosis it is cleaved into a 18-kDa fragment (p18-cyclin E) by caspases and it can no longer bind to the CDKs. Overexpression of Bcl2 protein downregulated the apoptotic process and at the same time reduced the expression of p18-cyclin E (Mazumder et al, 2002). These results throw some light on the roles of cyclin E in apoptosis.…”
Section: Pro-and Anti-apoptotic Effects Of Cyclinsmentioning
confidence: 90%
“…Recent investigations revealed that cyclin E is responsible for induction of apoptosis in hematopoietic cells (Mazumder et al, 2002). Cyclin E activity is increased substantially in the apoptotic process mediated by irradiation of RPMI 8226 cells.…”
Section: Pro-and Anti-apoptotic Effects Of Cyclinsmentioning
confidence: 99%
“…If the level of cyclin E is insufficient, cell cycle arrest at G1/S occurs, while too much cyclin E results in premature entry into S phase, mutations, and genomic instability (Spruck et al, 1999). Irradiation of hematopoietic cancer cells was found to increase cyclin E levels in a time-and dose-dependent manner (Mazumder et al, 2000;Mazumder et al, 2002), and this could influence cell cycle arrest. Importantly, mutations in the F box protein hCDC4 have been implicated in the pathogenesis of various forms of cancer and may be responsible for some cases of elevated cyclin E levels that are frequently associated with human cancers (Koepp et al, 2001;.…”
Section: Cell Cyclementioning
confidence: 99%
“…Levels and cleavage products of various cyclins have been implicated in apoptosis induction (Finkielstein et al, 2002;Mazumder et al, 2002). Also, accumulation of CDKI P27 Kip1 and cyclin E in mice deficient in its E3 ligase Skp2 results in increased spontaneous apoptosis (Nakayama et al, 2000), and the level of Skp2 in gastric carcinomas modulates the phenotype of the cancer, presumably by affecting P27 expression (Masuda et al, 2002).…”
Section: Cell Deathmentioning
confidence: 99%